Metabolic folate profiling as a function of time during cultivation suggests potential C2-metabolism in Saccharomyces cerevisiae - Schillert, Lena; Wirtz, Daniela; Weber, Nadine; Schaller, Franziska; Striegel, Lisa; Schmitt-Kopplin, Philippe; Rychlik, Michael (Frontiers in Nutrition, 2022)
Yeasts are reported to be rich in folates, a group of vitamers known to be involved in several biosynthetic reactions such as methylation reactions, oxidation and reduction processes, and nucleotide synthesis. Not being able to synthesize folates, humans rely on external folate supply. Here, we show the application of LC/MS-MS methods using SIDA (stable isotope dilution analysis) assays for the quantitative analysis of different folate mono- and polyglutamates during growth of Saccharomyces cerevisiae. Molecular networking (MN) was applied for detailed analysis of further folate metabolites. Highest folate contents of 13120 µg/100 g were observed after 20 h of cultivation. The main vitamers 5-CH3-H4folate and H4folate decreased during cultivation, while 5-CHO-H4folate showed increasing tendencyincreased during cultivation. The hexa- and heptaglutamate of 5-CH3-H4folate accounted for >96% of the total 5-CH3-H4folate content. A shift of the major polyglutamate from hexa- to heptaglutamate was observed after 29 h. MN unraveled two groups of novel folates which could be assigned to a potentially existing C2-metabolism in yeast. In detail, 5,10-ethenyl-tetrahydrofolate and a further CO-substituted 5-CH3-H4folate were identified as hexa- and heptaglutamates. The latter was neither identified as 5-acetyl-tetrahydrofolate nor as EthylFox, the oxidation product of 5-ethyl-tetrahydrofolate. The structure needs to be elucidated in future studies.